Pembangunan Sebagai Proses Eksklusi: Kajian Hukum Dan Ekonomi-Politik Atas Proyek Strategis Nasional - Wardana, Agung; Darmawardana, Dzaki Aribawa (Jurnal Hukum & Pembangunan, 2024)
Indonesia’s National Strategic Project (NSP) is a priority development agenda of Joko Widodo’s administration. Claiming to serve the public interest, they impact people's livelihoods in order to produce new spaces for the circulation of capital. This article aims to examine PSN by situating it within development discourse and practice. The authors argue that PSN is a mode of development that works through the power of exclusion because it is derived from certain assumptions about class, race, and gender, resulting in different consequences among social groups in society that have unequal power relations. Therefore, the authors suggests that a critical examination of the PSN should be conducted by analysing its four exclusionary powers: market, regulation, legitimacy, and coercion. This is because the interaction of these powers allows PSN to operate through the passive consent of the wider public and simultaneously weakens resistance from affected communities and civil society groups.